Making components with controlled metal deposition - Ribeiro, A. Fernando (1997)
Rapid Prototyping is a recent CAD/CAM/CIM based manufacturing technique which produces prototypes of components in a fraction of the time. This technique works by first drawing the part as a 3 Dimensional solid model using a CAD program and then ‘printing’ it in 3 Dimensions. The raw material can be a photopolymer or thermoplastic which solidifies when in contact with light. Other materials are available although 100% metal is not a very usual one. This paper presents a new approach for a Rapid Prototyping technique which uses Robot Fusion Welding. The component is drawn as a 3D solid in a CAD package, and this is then electronically sliced in order to automatically generate the robot path. The welding parameters are also generated according to the desired material/thickness of the component. By serial link RS-232-C, the robot program is then downloaded. This process works unmanned and proved to be good enough for the purpose. This technique can be used to make not only the prototype but also the final component with the desired metal. Therefore, this represents also a new production technique more suitable for low volume production. Another advantage with this new technique is that different metals can be used during the build up of the component to achieve different structural characteristics in different parts of the same component. This would not be possible with casting. The welding can be stopped at any time, the filler material changed, and the welding started again. The wire can be changed quickly. The process created is hereby described as well as its advantages and disadvantages. Some case studies are carried out and described. Several other case studies were carried out and published in order to fully test this system and some references are made to those publications in section IV.